2021
DOI: 10.1186/s12889-021-11946-8
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of quality of village-level care and patients’ healthcare-seeking behaviors in rural China

Abstract: Background Although the progress in global health initiatives has improved the availability of primary health care (PHC), unqualified healthcare remains a serious challenge in low- and middle-income countries, where PHC is often underutilized. This study examines factors associated with patients’ healthcare-seeking behaviors in rural Chin—seeking healthcare at village-level PHC providers, at higher-level health facilities, self-medicating, and refraining from seeking medical help. We focus on p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 36 publications
2
7
0
Order By: Relevance
“…Our results show the poor common disease management competencies of PCPs in the three counties of Sichuan. Considering these two symptoms are common, the result indicated the overall services they deliver may not be satisfying, which has also been shown by previous studies [ 19 , 20 , 21 , 22 ]. One surprising result is that even though GPs are equipped with low-level medical knowledge, they are still able to correctly manage case vignettes in terms of diagnoses and treatment, considering their performances in these two scales are relatively acceptable (12.3% incorrect rate).…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Our results show the poor common disease management competencies of PCPs in the three counties of Sichuan. Considering these two symptoms are common, the result indicated the overall services they deliver may not be satisfying, which has also been shown by previous studies [ 19 , 20 , 21 , 22 ]. One surprising result is that even though GPs are equipped with low-level medical knowledge, they are still able to correctly manage case vignettes in terms of diagnoses and treatment, considering their performances in these two scales are relatively acceptable (12.3% incorrect rate).…”
Section: Discussionsupporting
confidence: 67%
“…Many research studies have used vignettes to evaluate PCPs’ competency in other developing countries [ 17 , 18 ], but this field is still under-researched in China. The only four studies using vignettes demonstrated poor competencies of village clinicians [ 19 , 20 , 21 , 22 ], but did not evaluate GPs in THCs, which may not represent the overall situation of PCPs in China.…”
Section: Introductionmentioning
confidence: 99%
“…A possible explanation could be the inconsistency between the objective quality of healthcare provided and the subjective quality perceived by patients 47 ; therefore, to improve service quality, patients should identify the actual quality of primary health care precisely and then improve their satisfaction, thereby promoting the more efficient use of primary-level health resources.…”
Section: Discussionmentioning
confidence: 99%
“…(2) Drug supply. The availability and variety of drugs are also influential factors in patients' preference of care 20 . Concerns about the guaranteed availability and quality of drugs can drive patients to switch to high-level hospitals 21 .…”
Section: Theoretical and Hypotheses Developmentmentioning
confidence: 99%